The urban church imagined : religion, race, and authenticity in the city - Barron, Jessica M.; Williams, Rhys H. (New York : New York University Press, 2017)
The Urban Church Imagined illuminates the dynamics surrounding white urban evangelical congregations' approaches to organizational vitality and diversifying membership. Many evangelical churches are moving to urban, downtown areas to build their congregations and attract younger, millennial members. The urban environment fosters two expectations. First, a deep familiarity and reverence for popular consumer culture, and second, the presence of racial diversity. Church leaders use these ideas when they imagine what a "city church" should look like, but they must balance that with what it actually takes to make this happen. In part, racial diversity is seen as key to urban churches presenting themselves as "in touch" and "authentic." Yet, in an effort to seduce religious consumers, church leaders often and inadvertently end up reproducing racial and economic inequality, an unexpected contradiction to their goal of inclusivity. Drawing on several years of research, Jessica M. Barron and Rhys H. Williams explore the cultural contours of one such church in downtown Chicago. They show that church leaders and congregants' understandings of the connections between race, consumer culture, and the city is a motivating factor for many members who value interracial interactions as a part of their worship experience. But these explorations often unintentionally exclude members along racial and classed lines.
Introduction: Race, church, city -- City Jesus -- Urban outfitters -- The diversity list -- City outreach -- "Swirl babies" -- "Should I stay or should I go?" -- Conclusion: The city imagined.
Includes bibliographical references and index.
Keywords: City churches; City churches; SOCIAL SCIENCE / Sociology of Religion